Reinventing spaces as places of life and peace, a playful strategy for vulnerable sectors - Nuñez-Ríos, Greys; García- Mendoza, Kadry; Castillo-Martelo, Judith; Niño-Jiménez, Nevis (Política, Globalidad y Ciudadanía, 2020)
This article is the product of an action-participatory research, the objective of which was to intervene in a community in a vulnerable and marginal sector of the city of Barranquilla, in economic, social and physical aspects, with playful-pedagogical strategies to transform the spaces of these exposed areas in places of life and peace, which from the social dynamics invite the strengthening of citizen participation and competences, emotional intelligence and environmental culture. It was approached from a qualitative paradigm with a non-experimental and field design, with a transversal descriptive scope. After the intervention, it was found that the community is motivated to participate in activities that seek to generate a culture of peace for the encounter and collective enjoyment where its actors reinvent their relationships and transform the fundamental categories that govern their daily lives. It is concluded that these interventions are an opportunity to bring the population closer to the development of their environmental competencies, sensitize them to the environmental impact and their commitment to sustainable development; as well as enhancing their affective development, generating transformation of life stories articulating reading and oral narration to impact the man-society-nature relationship.